(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Porous asphalt pavement is a particular asphalt mixture made up of both fine and coarse aggregates bonded by a bituminous binder. Although it has a rougher texture, porous asphalt looks like conventional asphalt on the outside. In the past decade, porous asphalt pavement has gained popularity as a storm water best management practice and utilize similar mixtures as those used for open-graded friction courses. Additive materials such as fly ash, coal ash, and many more had been widely used successfully in the original specification of porous asphalt mixtures to improve their durability and rutting resistance performance. In this study, fly ash has been used to replace aggregate dust and the aggregate gradation limit in the porous asphalt mixture to determine the Optimum Bitumen Content (OBC) as well as to improve rutting resistance and durability. The OBC was then determined for all the mixes by Marshall Mix design. Laboratory specimens were prepared using 75 blows of the Marshall hammer per side. The OBC for the conventional porous asphalt mix with aggregate dust was found to be 6 percent, while the OBC for the modified porous asphalt mix with fly ash was found to be 5 percent. Rut depth for porous asphalt mixes with aggregate dust was lower (1.6 mm) compared with porous asphalt mixes with fly ash (1.93 mm). This indicates that the additive material could efficiently retain the binder in the mix. As a result, fly ash could be used as an alternative to aggregate dust in the porous asphalt mixture.